2021
DOI: 10.1523/eneuro.0404-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Arcuate Angiotensin II Increases Arterial Pressure via Coordinated Increases in Sympathetic Nerve Activity and Vasopressin Secretion

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…The local RAS within the ARC is implicated in the integrated control of energy expenditure and may also contribute to blood pressure control ( Claflin et al, 2017 ; Shi et al, 2017 , 2021 , 2022 ; Morselli et al, 2018 ). Previous work demonstrates that DOCA-salt stimulates both energy expenditure and blood pressure through mechanisms that involve the brain RAS, and increasing evidence supports a major role for the ARC RAS in the integrated control of energy expenditure in response to various stimuli through the actions of AT 1 R within selected AgRP neurons ( Itaya et al, 1986 ; Kubo et al, 2000 ; Park and Leenen, 2001 ; Grobe et al, 2011 ; Claflin et al, 2017 ; Morselli et al, 2018 ; Oliveira et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The local RAS within the ARC is implicated in the integrated control of energy expenditure and may also contribute to blood pressure control ( Claflin et al, 2017 ; Shi et al, 2017 , 2021 , 2022 ; Morselli et al, 2018 ). Previous work demonstrates that DOCA-salt stimulates both energy expenditure and blood pressure through mechanisms that involve the brain RAS, and increasing evidence supports a major role for the ARC RAS in the integrated control of energy expenditure in response to various stimuli through the actions of AT 1 R within selected AgRP neurons ( Itaya et al, 1986 ; Kubo et al, 2000 ; Park and Leenen, 2001 ; Grobe et al, 2011 ; Claflin et al, 2017 ; Morselli et al, 2018 ; Oliveira et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesized mechanism involves the actions of the renin-angiotensin system (RAS) in the brain, since the sympathoexcitatory and hypertensive actions of leptin require functional AngII type 1 receptors (AT1aR), whereas the anorexic effects apparently do not [24,146] (Figure 2). Similar to leptin and insulin, AngII in the ArcN increased SNA and blood pressure [158,159] in male rats through binding to AT1aR; the downstream pathway depended upon inhibition of NPY and stimulation of POMC neurons that project to the PVN [159]. A detailed neuroanatomical assessment of the location of AT1aR in the ArcN of male rats [159,160] revealed that (1) approximately 10% of AT1aR were expressed on NPY neurons; (2) AT1aR were rarely found on POMC neurons (4%); (3) instead, AT1aR were expressed largely in neurons that co-expressed both tyrosine hydroxylase (TyH; dopaminergic) and VGat2 (GABAergic) (see also ref.…”
Section: Selective Leptin Resistance In the Arcn: Preserved Leptin-in...mentioning
confidence: 99%
“…Similar to leptin and insulin, AngII in the ArcN increased SNA and blood pressure [158,159] in male rats through binding to AT1aR; the downstream pathway depended upon inhibition of NPY and stimulation of POMC neurons that project to the PVN [159]. A detailed neuroanatomical assessment of the location of AT1aR in the ArcN of male rats [159,160] revealed that (1) approximately 10% of AT1aR were expressed on NPY neurons; (2) AT1aR were rarely found on POMC neurons (4%); (3) instead, AT1aR were expressed largely in neurons that co-expressed both tyrosine hydroxylase (TyH; dopaminergic) and VGat2 (GABAergic) (see also ref. [161]); (4) LepR positive neurons rarely co-expressed AT1aR.…”
Section: Selective Leptin Resistance In the Arcn: Preserved Leptin-in...mentioning
confidence: 99%